2022
DOI: 10.1093/jxb/erac336
|View full text |Cite
|
Sign up to set email alerts
|

Genetic modification of PIN genes induces causal mechanisms of stay-green drought adaptation phenotype

Abstract: The stay-green trait is recognised as a key drought adaptation mechanism in cereals worldwide. Stay-green sorghum plants exhibit delayed senescence of leaves and stems, leading to prolonged growth, a reduced risk of lodging and higher grain yield under end-of-season drought stress. More than 45 quantitative trait loci (QTL) associated with stay-green have been identified, including two major QTL (Stg1 and Stg2). However, none of the contributing genes that regulate functional stay-green are known. Here we show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
4
1

Relationship

3
6

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 63 publications
0
15
0
Order By: Relevance
“…Four major QTLs, namely Stg1-4 derived from BTx642, have been identified. Detailed analysis revealed the presence of multiple PIN FORMED family of auxin efflux carrier genes within these QTLs, such as the Stg1 ( SbPIN4 ), Stg2 ( SbPIN2 ), and Stg3b ( SbPIN1 ) (Borrell et al ., 2022). Similarly, cytokinin biosynthetic genes delay senescence in Arabidopsis and sorghum, probably due to increased activity of cell wall invertase ( CWINV ), a gene that affects the leaf source/sink balance (Markovich et al ., 2017).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Four major QTLs, namely Stg1-4 derived from BTx642, have been identified. Detailed analysis revealed the presence of multiple PIN FORMED family of auxin efflux carrier genes within these QTLs, such as the Stg1 ( SbPIN4 ), Stg2 ( SbPIN2 ), and Stg3b ( SbPIN1 ) (Borrell et al ., 2022). Similarly, cytokinin biosynthetic genes delay senescence in Arabidopsis and sorghum, probably due to increased activity of cell wall invertase ( CWINV ), a gene that affects the leaf source/sink balance (Markovich et al ., 2017).…”
Section: Resultsmentioning
confidence: 99%
“…Recent studies have demonstrated the significant role of both cytokinin and auxin in stay-green phenotypes in sorghum (Markovich et al ., 2017; Borrell et al ., 2022). Stay-green traits enable plants to retain green leaves and stems, thus maintaining longer growth during the end of the drought season (Borrell et al ., 2000).…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, previous studies in sorghum have also reported co‒ locations of genetic loci for stay‒green traits and root angle (Mace et al, 2012; Borrell et al, 2014). Since one of the important mechanisms underlying stay‒green is associated with increased post‒flowering water uptake in terminal drought environments, a root system with a steep angle should result in a deep rooting system that enhances access to deep soil water (Manschadi, Christopher, Devoil, & Hammer, 2006; Singh, van Oosterom, Jordan, & Hammer, 2012; Borrell et al, 2014; Borrell et al, 2022). Therefore, SRA may be a major determinant of the mature RSA, making it a promising candidate for selection that can be conducted in the early growth stages to accelerate the breeding process.…”
Section: Introductionmentioning
confidence: 99%
“…Indirect effects can be seen in the dynamic balance of allometry where growth of one organ influences another. For example, the canopy has an allometric relationship with the root system, where increases in the canopy biomass correlates with increased root biomass (Borrell et al 2022). As PIN2 expression is almost exclusively within the roots, the possibility of root specific architectural changes, independent of above- and below-ground allometry, provides an interesting subject for investigation (Müller et al 1998).…”
Section: Introductionmentioning
confidence: 99%